Havesting Bananas - (:unkn) unknown (The Imperial Institute, 2009)
Labourers havesting bunches of bananas from a field.
Colour: Black and White; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Harvesting--Trinidad and Tobago; Working class--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago